A study on the intrapapillary capillary loop detected by narrow band imaging system in early oral squamous cell carcinoma. Issue 5 (September 2015) - Sekine, Riyo; Yakushiji, Takashi; Tanaka, Youichi; Shibahara, Takahiko
Abstract: Objective: The purpose of this study is to determine the effectiveness of narrow band imaging (NBI) by analyzing three-dimensional (3D) images of intrapapillary capillary loop (IPCL) and recording changes over time. Methods: This study was conducted between April 2007 and October 2011 at the Department of Oral and Maxillofacial Surgery of Tokyo Dental College Chiba Hospital. A total of 119 cases and 40 healthy volunteers were observed with NBI. Within a total of 119 cases oral squamous cell carcinoma (OSCC) was diagnosed in 48 cases (40%), leukoplakia in 26 cases (22%), oral lichen planus in 18 cases (15%), gingivitis in 5 cases (4%), aphtha in 4 cases (3.5%), ulcer in 4 cases (3.5%), erythroplakia in 3 cases (2.5%), pigmentation in 3 cases (2.5%), and other diseases in 8 cases (7%). The 40 healthy volunteers were medically examined at the regions of the gingiva, lower lip, buccal mucosa, oral floor, lateral border of the tongue, and dorsal surface of the tongue. Results: Morphological changes of IPCL were analyzed through the construction of 3D images. The dimension, volume and density of vascular vessel were compared between OSCC, dysplasia and normal mucosa. Abnormal vascular vessels were apparent in cases of dysplasia and OSCC when examined through magnifying endoscopy with NBI. Morphological changes of IPCL such as dilation, aggregation and thickness increasing observed by NBI were certified through 3D imaging. Conclusions: These results suggest that NBI is an effective method for the early detection of OSCC.